PEMODELAN SPASIAL DISTRIBUSI KARBON MONOKSIDA DI KOTA BANDUNG - Arista, Faza; Saraswati, Ratna; Wibowo, Adi (UI Scholars Hub, 2019)
Air pollution is a significant problem in many urban areas. WHO declares 91% of people in the world breathe unhealthy air. Bandung, as a metropolitan city continues to experience increased population growth is causing an increase in the land area, woke up and dropped in the green area. The raises the problem of the decline in air quality. This research aims to analyze the spatial distribution of pollutants in Bandung City and its relation to distribution patterns of land surface temperature, the building density, and density of vegetation. The data used in the form of pollutant levels and Landsat 8 images in the dry month of 2018. The methods used in the study of spatial interpolation methods of the form IDW, LST, NDBI, and NDVI. Statistical tests using correlation and regression. The results showed that the spatial distribution of CO concentrations showed a pattern that was spread almost the same in the dry month of 2018, namely at a relatively high land surface temperature and building density and relatively low vegetation density, high levels of pollutants. The results of statistical tests declared land surface temperature, the density of buildings and vegetation density correlated moderate level against the distribution of CO and regression results declared land surface temperature, the density of buildings and vegetation density there are influences that significantly to the distribution of CO.